Terrestrisch beeinflußte Wolkenformen auf Satellitenbildern Mitteleuropas - Wiesner, Klaus; Fezer, Fritz (ERDKUNDE, 1979)
The interpretation of multispectral photos from the ERT satellite LANDSAT-1, launched on its polar orbit from Vandenberg in California on 23.7.72, also produced new findings in the field of weather research, backed up by shots from the weather satellites TIROS IV and ESS A 8. Vertical LANDSAT photos show, through moderate cloud formation, both land relief and the shape of clouds, thus providing a new opening for topoclimatology. Relief has a crucial influence on the formation of many cloud shapes, varying in accordance with the range of relief forms. Such orographic clouds are, so to speak, linked to the earth’s relief, which is why their position is generally stationary. The best known examples are cloud banks, cap clouds, wavy and cylindrical-shaped clouds. Wavy clouds behind mountains may, according to recent findings, be caused both by stable air-waves and travelling unstable Kelvin-Helmholtz waves. All these waves usually have their maximum amplitude in the lower or middle troposphere, frequently directly over the mountains which produce them. Wave patterns may be observed in the lower stratus layers on the LANDSAT photos: they arose through a lee effect over hilly terrain. It was surprising to discern wave clouds in the lee of a medium-high mountain range at a distance of 200-300 km and with an altitude of 6000-8000 metres. The commonest cloud type on the LANDSAT pictures are cumulus rows, however. These form both over mountain ranges and highlands and over plains, coasts and the sea. They probably originate in vibrations in the lower troposphere due to varying temperatures of the earth’s surface. Although such cumulus clouds occur over all kinds of relief, in many cases the relief controls the arrangement. Thick swelling clouds arise over mountains and highlands due to increased convection. Vegetation level and surface composition also have an effect e.g. cumulus clouds are likely in moor and grassland regions, and over extended woodlands. Besides these rough relationships between cumulus rows and large relief units - mountain ranges, plains, coasts - the photos show a clear correlation between the formation of cumuli and rows and the presence of individual massifs, crests and knolls. Chains of congested clouds arise far into the lowlands of mountain ranges. Often single cumuli or cloud-chains adorn the banks of highland rivers, too. Mountain ranges and steeply rising islands have a reverse effect on stratus clouds: while they further the formation of cumulus clouds, sheet clouds are dispersed. The dependence on relief is also evident from the pictures in the case of fog. In hilly country it covers valleys, gullies, pools and troughs in the morning, leaving knolls free. Fog often indicates lines of current, suggesting direction of flow. Single protruding rocks or other elevations produce fog waves. In flat terrain moors, damp depressions and marshy areas around rivers create fog. Over industrial areas, towns and motorways fogs are dispersed by warmth emission, but enhanced by smoke. These findings allow not only the correlation of cloud forms and terrestrial relief but they even help to identify mountains and valleys on satellite photos. For pictures from weather satellites the characteristic cloud shapes over single mountains and islands provide additional adjustment points. If a photo is veiled by low stratus clouds and fog, elevations and islands can be localized as dark points or patches since they disperse the strati in places or break through them. Lakes, towns and industrial sites have a similar effect. If the blind-flight-system breaks down or a small plane suddenly rises above the clouds, emergency navigation might be possible through recognizing these cloud features. LANDSAT-C, the third satellite of this series, has an extraordinarily good resolution of 40 to 50 m. This allows agriculture and regional planning (lay-out of housing areas, building motorways etc) to discover unsuitable, fog threatened areas.